2021
DOI: 10.1108/ijchm-07-2021-0899
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant management and food waste reduction: factors affecting attitudes and intentions in restaurants of Spain

Abstract: Purpose Although the challenge of food waste (FW) in the foodservice sector is significant, restaurant managers do not always engage in its reduction. The psychological reasons for this disengagement remain insufficiently understood. This study aims to explore the antecedents of behavioural intention of restaurateurs (not) to reduce FW. The influence of three factors is tested, namely, market orientation; environmental apathy alongside selected neutralization techniques, namely, appeal to higher loyalties; den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 119 publications
(186 reference statements)
0
9
0
2
Order By: Relevance
“…According to Hu and Bentler (1999) and Dijkstra and Henseler (2015), an SRMR value of less than .10 or .08 is viewed as a valid fit, and our model met this threshold. The suitability of the study was determined by comparing the differences between the saturated values of (d_ULS and d_G) with the estimated values of (d_ULS and d_G) at a confidence interval of 95% (Filimonau et al, 2022). There were no differences between the saturated values and the estimated values, thus indicating the suitability of our study model (Hair et al, 2017).…”
Section: Smartpls Test For the Model Fitmentioning
confidence: 92%
“…According to Hu and Bentler (1999) and Dijkstra and Henseler (2015), an SRMR value of less than .10 or .08 is viewed as a valid fit, and our model met this threshold. The suitability of the study was determined by comparing the differences between the saturated values of (d_ULS and d_G) with the estimated values of (d_ULS and d_G) at a confidence interval of 95% (Filimonau et al, 2022). There were no differences between the saturated values and the estimated values, thus indicating the suitability of our study model (Hair et al, 2017).…”
Section: Smartpls Test For the Model Fitmentioning
confidence: 92%
“…Dalam konteks etika, keberadaan FLW menjadi permasalahan karena sikap membuang buang makanan dianggap tidak dapat diterima dalam berbagai perspektif. Filimonau et al, (2022) menggunakan tiga teknik netralisasi untuk mengukur tingkat perilaku manager restoran dalam pengelolaan limbah. Teori tersebut menunjukkan appear to higher loyalty dan denial to injury, yang digunakan ketika menjelaskan mengapa tantangan food waste di sektor jasa makanan tetap tidak dikelola dengan baik.…”
Section: Teori Netralisasiunclassified
“…Penelitian ini menggunakan MFCA sebagai alat kuantifikasi limbah sebagai alat inovatif membantu bisnis makanan mengidentifikasi dan mengelola aliran limbahnya. Selain itu keberadaan food loss dan food waste tidak dapat dipisahkan dari peran manajer dalam pengelolaan (Filimonau et al, 2022). Keputusan manajerial pada sebagian besar proses aktifitas operasional berpengaruh terhadap food loss dan food waste yang.…”
unclassified
“…Those customers would be willing to pay a premium for eco-friendly menu items. Filimonau et al (2022) proposed that restaurant managers can search for influential factors that affect customers’ food choices to develop menus based on EC, ultimately leading to better performance. Karatepe et al (2021) also found that green practices were conducted differently according to managers’ environmental–cognitive views.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another research stream has investigated restaurant management’s environmental value by focusing on its impact on internal organizational factors (e.g. employees’ environmental commitment and performance and green brand image) (Bouzari et al , 2022; Filimonau et al , 2022). However, those existing studies have yet to encompass external organizational factors that can be initiated by restaurant management’s EC, ultimately providing novel knowledge about how to operate restaurants for better environmental performance.…”
Section: Introductionmentioning
confidence: 99%